The role of rules-based compliance systems in the new EU regulatory landscape. Issue 6 (7th October 2014) - Gozman, Daniel; Currie, Wendy
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to understand how institutional changes to the European Union regulatory landscape may affect corresponding institutionalized operational practices within financial organizations. Design/methodology/approach – The study adopts an Investment Management System as its case and investigates different implementations of this system within eight financial organizations, predominantly focused on investment banking and asset management activities within capital markets. At the systems vendor site, senior systems consultants and client relationship managers were interviewed. Within the financial organizations, compliance, risk and systems experts were interviewed. Findings – The study empirically tests modes of institutional change. Displacement and Layering were found to be the most prevalent modes. However, the study highlights how the outcomes of Displacement and Drift may be similar in effect as both modes may cause compliance gaps. The research highlights how changes in regulations may create gaps in systems and processes which, in the short term, need to be plugged by manual processes. Practical implications – Vendors abilities to manage institutional change caused by Drift, Displacement, Layering and Conversion and their ability to efficiently and quickly translate institutional variables into structured systems has the power to ease the pain and cost of compliance as well as reducing the risk of breeches by reducing the need for interim manual systems. Originality/value – The study makes a contribution by applying recent theoretical concepts of institutional change to the topic of regulatory change uses this analysis to provide insight into the effects of this new environment.